Study protocol for reducing childbirth fear: a midwife-led psycho-education intervention - Fenwick, Jennifer (BioMed Central, 2013)
BACKGROUND: Childbirth fear has received considerable attention in Scandinavian countries, and the United Kingdom, but not in Australia. For first-time mothers, fear is often linked to a perceived lack of control and disbelief in the body’s ability to give birth safely, whereas multiparous women may be fearful as a result of previous negative and/or traumatic birth experiences. There have been few well-designed intervention studies that test interventions to address women’s childbirth fear, support normal birth, and diminish the possibility of a negative birth experience. METHODS/DESIGN: Pregnant women in their second trimester of pregnancy will be recruited and screened from antenatal clinics in Queensland, Australia. Women reporting high childbirth fear will be randomly allocated to the intervention or control group. The psycho-educational intervention is offered by midwives over the telephone at 24 and 34 weeks of pregnancy. The intervention aims to review birth expectations, work through distressing elements of childbirth, discuss strategies to develop support networks, affirm that negative childbirth events can be managed and develop a birth plan. Women in the control group will receive standard care offered by the public funded maternity services in Australia. All women will receive an information booklet on childbirth choices. Data will be collected at recruitment during the second trimester, 36 weeks of pregnancy, and 4–6 weeks after birth. DISCUSSION: This study aims to test the efficacy of a brief, midwife-led psycho-education counselling (known as BELIEF: Birth Emotions - Looking to Improve Expectant Fear) to reduce women’s childbirth fear. 1) Relative to controls, women receiving BELIEF will report lower levels of childbirth fear at term; 2) less decisional conflict; 3) less depressive symptoms; 4) better childbirth self-efficacy; and 5) improved health and obstetric outcomes. TRIAL REGISTRATION: Australian New Zealand Controlled Trials Registry ACTRN12612000526875.